Implementation of Finite State Machine Algorithm for Interactive Physics Learning in a 3D Game - Nugraha, Nur Budi; Santosa, Yaqutina Marjani; Mulyani, Esti (Politeknik Negeri Batam, 2023)
Physics is a subject taught in high schools as per the established curriculum. Teachers often employ traditional teaching methods where students study independently without active participation, leading to boredom and reduced enthusiasm for learning. Physics is frequently perceived as difficult and perplexing by most students, and the utilization of 3D games as a learning tool can help overcome these challenges. This research aims to integrate the Finite State Machine (FSM) algorithm into a 3D game to create a more effective and engaging learning experience for students. The study employs the waterfall method in application development, encompassing stages such as needs analysis, application design, FSM implementation in games, and game testing and evaluation. 3D physics games have been successfully developed and tested for their feasibility. This game serves as an effective means of entertainment and learning, aiding students in enhancing their understanding of physics subjects. According to the results of a questionnaire with 50 respondents, it is evident that this 3D game is quite user-friendly (90%) and possesses a very good user interface (89%). Approximately 78% of respondents stated that their experience in using the game was very good. Moreover, 82% of respondents found that this educational physics game was highly beneficial for learning physics material.